Time-specific and Cumulative Effects of Exposure to Parental Externalizing Behavior on Risk for Young Adult Alcohol Use Disorder - Edwards, Alexis C. (Addict Behav, 2017)
BACKGROUND: Previous studies indicate that parental externalizing behavior (EB) is a robust risk factor for alcohol use disorder (AUD) in their children, and that this is due to both inherited genetic liability and environmental exposure. However, it remains unclear whether the effects of exposure to parental EB vary as a function of timing and/or chronicity. METHODS: We identified biological parents with an alcohol use disorder, drug abuse, or criminal behavior, during different periods of their child’s upbringing, using Swedish national registries. Logistic regression was used to determine whether the effect of parental EB exposure during different developmental periods differentially impacted children’s risk for young adult AUD (ages 19–24). In addition, we tested how multiply affected parents and/or sustained exposure to affected parents impacted risk. RESULTS: While parental EB increased risk for young adult AUD, timing of exposure did not differentially impact risk. Having a second affected parent increased the risk of AUD additionally, and sustained exposure to parental EB across multiple periods resulted in a higher risk of young adult AUD than exposure in only one period. CONCLUSIONS: In this well-powered population study, there was no evidence of “sensitive periods” of exposure to national registry-ascertained parental EB with respect to impact on young adult AUD, but sustained exposure was more pathogenic than limited exposure. These findings suggest developmental timing does not meaningfully vary the impact, but rather there is a pervasive risk for development of young adult AUD for children and adolescents exposed to parental EB.